The Impact of Employee’s Income Grades on Tourism Demand: : An Exploratory Study About Employees Opinion to Their Demand of Tourism in Koya Technical Institute /Iraq - Sharif, Dlshad A.; Abdullah , Sarkar A.; Othman, Bestoon A.; Abdullah, Yakaw H. (Polytechnic Journal of Humanities and Social Sciences, 2024)
This study aims to explore the impact of employee’s income on tourism demand. It is an exploratory study about employee’s opinion on tourism demand of the Koya Technical Institute in Koysinjaq city in Iraq. This study proposes to test the extent of availability of the employees demand toward tourism and characteristics of income or this study also proposes to test the extent of availability of the employees demand toward tourism and characteristics of income or salary grade in the administration of this institute. A questionnaire involving of 10 phrases has been set and distributed as the research sample, the size of the population of the study 220 employees at the Koya Technical Institute, out of them ten scientific departments such as medical, technological and management are selected randomly. Otherwise the total of 120 questionnaires have been distributed, all of them have been returned and analyzed, the following appropriate statistical methods are used to analyze data and to test research hypotheses such as, Frequencies, Sum, Mean, Percentages, and Compare Mean One-Sample T- test, Pearson Correlation is also used to test the correlation between dependent and independent variables. The main conclusion of the study is the income and salary grades has an impact on tourism demand in all dimensions. And income has a great and significant effect on tourism demand of Koya Technical Institute. With these findings the research offered several recommendations such as there is need of improvement of tourism sector.